Creacion de un diplomado en gerencia de transformacion digital en una universidad peruana para capacitar profesionales en gerencia de transformación digital” - Cabanillas Lopez, Walter Adolfo (2023)
This work sufficiency paper is based on the experience of researching, evaluating, documenting, and proposing the need to provide educational products on the digital transformation of companies and how to manage these processes based on the need of the business ecosystem. nationals to professionals who lead companies or who are going to be facilitators of digital transformation processes in the companies where they work. Investigating how the Peruvian business community has internalized the need to be focused on the client and use technology, has educated its professionals to create an environment of innovation and acceptance of change, has had a small evolution in how decisions are made and they create strategies based on data, among others, it was evidenced that this ecosystem needs to learn about the digital transformation of companies and how to manage it. This document provides clear knowledge that facilitates the reader what to learn in order to be clear about how to manage a digital transformation of a company shown through an educational program under the educational legislation of the government of Peru. In addition, it allows us to understand the importance of creating these educational products in the country's universities to accelerate the digital transformation process. In conclusion, the need to create digital transformation management diplomas in Peruvian universities, whether public or private, is evident.